Novel variant of the glycerol-3-phosphate dehydrogenase-1 Like (GPD1-L) gene in Japanese Brugada syndrome patients. (14th October 2021) - Usuda, K; Hayashi, K; Ishikawa, T; Aizawa, Y; Kato, T; Kusayama, T; Tsuda, T; Usui, S; Sakata, K; Kawashiri, M; Mishima, H; Yoshiura, K; et al.
Abstract: Background: The incidence of Brugada syndrome (BrS) varies among racial groups. Several studies reported Glycerol-3-Phosphate Dehydrogenase 1-Like (GPD1-L) gene is associated with BrS. However, most of these studies were reported from Western countries, so the evidence about GPD1-L mutation is limited especially among Asian BrS patients. This study aimed to search for rare variants in GPD1-L among Japanese BrS patients and to investigate the pathogenicity. Method: We performed whole-exome sequencing for patients with Brugada type 1 ECG pattern from Japanese multicenter BrS cohort consisting of SCN5A-negative BrS probands (n=288) and controls (n=372). We conducted patch-clamp study in human embryonic kidney (HEK) 293 cells cotransfected with the wild-type sodium channel (SCN5A) and wild-type or mutant GPD1-L expression plasmid. Results: We identified a rare variant in GPD1-L, p.D262N (c.784g>a) in 2 of 288 BrS probands, which was not identified in 372 controls. The minor allele frequency of the variant is 0.0014% in the Genome Aggregation Database. One proband was a 49-year-old man and the other was 34-year-old man who both developed a ventricular fibrillation. ECGs of both probands showed Brugada Type 1 pattern after administration of the pilsicainide. In functional study, coexpression of D262N GPD1-L with SCN5A in HEK293 cells significantly reduced inward sodium currents compared with wild-type GPD1-L. Additionally, inward sodium currents with D262N were similar to those with A280V GPD1-L, which was associated with BrS in previous reports (Figure). Also, several pathogenicity prediction programs, such as SIFT (score: 0.031) and PolyPhen2 (score: 0.937) predicted deleterious effects of GPD1-L D262N. Conclusion: We identified a rare variant in GPD1-L at the rate of 0.7% in Japanese BrS patients without SCN5A mutations. GPD1-L, p.D262N reduces inward sodium currents and may be a novel susceptible variant for BrS in the Japanese population. Funding Acknowledgement: Type of funding sources: None.